A new method to solve the fully connected Reserve Network Design Problem - Jafari, Nahid; Hearne, John (European journal of operational research, 2013)
•We propose a new mixed integer programming model to solve the Reserve Network Design Problem.•The model is simpler in concept and in implementation than existing exact models.•The model enforces contiguity of selected sites.•With small changes to the basic formulation the model can handle various related problems. In selecting sites for conservation purposes connectivity of habitat is important for allowing species to move freely within a protected area. The aim of the Reserve Network Design Problem is to choose a network of contiguous sites which maximises some conservation objective subject to various constraints. The problem has been solved using both heuristic and exact methods. Heuristic methods can handle much larger problems than exact methods but cannot guarantee an optimal solution. Improvements in both computer power and optimisation algorithms have increased the attractiveness of exact methods. The aim of this work is to formulate an improved algorithm for solving the Reserve Network Design Problem. Based on the concept of the transshipment problem a mixed integer programming model is formulated that achieves contiguity of the selected sites. The model is simpler in concept and to implement than previous exact models and does not require any assumptions about the regular shape of candidate sites. The method easily handles the case where more than one reserve system is required. We illustrate this with an example obtaining the trade-off between the number of contiguous areas and utility. We also illustrate that the important property of compactness can be achieved while maintaining contiguity of selected sites.